Ileocecal junction perforation by colonic T-cell lymphoma in a patient with primary Sjögren's syndrome. Issue 4 (October 2020) - Liu, Xiao-Chuan; Jia, Zhi-Wei; Weng, Yan; Yang, Lian-Jun; Wang, Jing; Peng, Hao
Primary Sjögren's syndrome (pSS) is associated with an increased risk of lymphoma, especially non-Hodgkin's lymphoma. The rarest pathological subtype is T-cell lymphoma. We herein report a case of a 52-year-old man with a 17-year history of pSS who was admitted to our hospital with chronic epigastric pain and a positive fecal occult blood test. Colonoscopy revealed multiple colonic ulcers, and histological and immunological studies demonstrated the T-cell origin of this lymphoma. However, the patient rejected all treatments. He developed recurrent intestinal obstruction and infection for 3 years until an intestinal perforation occurred. The right half of the colon was resected and colostomy was performed. However, the patient died of an intestinal fistula and intraperitoneal infection 40 days postoperatively. This case highlights the rarity of the correlation between T-cell lymphoma and pSS.